Attributes of primary health care in Mato Grosso do Sul state: PCAT-Brazil paired for users and health professionals, 2018 - Rafael Aiello Bomfim; Hazelelponi Querã Naumann Cerqueira Leite; Edilson José Zafalon; Alessandro Diogo De-Carli; Mara Lisiane de Moraes dos Santos (BMC, 2022)
Abstract Objective The objective of the present study was to analyse the quality of adults and older adults health care in Primary Health Care (PHC) services in the State of Mato Grosso do Sul, 2018. Methods A quantitative survey was carried out in which the municipalities participating in the study included the four macro-regions following the Director Regional Plan (DRP). In this study, the quality of care was verified using the validated version of the PCAT-Br for adult and older adults users over 18 years of age and professionals. The professional's and users' views were compared between PHC attributes in the State of Mato Grosso do Sul. We performed the paired student t-test. STATA v.14.2 software (College Station, TX, USA) was used for the analyses. Sensitivity analysis was done to compare socio-demographic characteristics. Results Eight hundred twenty-five users and 424 professionals participated in the study. According to users, the Accessibility attribute had the worst performance in all macro-regions (mean score PCAT = 3.58). There were significant differences between the perception of users and professionals (PCAT = 5.32 for users and PCAT = 7.11 for professionals) in all attributes evaluated. Conclusions There was a difference in users' and professionals' perceptions between PHC attributes. Therefore, it is necessary to strengthen PHC care networks in the State, mainly considering the users' perspectives.